Foto do dia ou microcrônica verbo-visual: um gênero na perspectiva da Escola de Sydney - Gehrke, Nara Augustin (2015)
This research establishes a new genre termed micro verbal-visual chronic. It is proposed that it can be approached from the perspective of Sydney School as one genre of the family of story genres (MARTIN; ROSE, 2008, 2012). To prove this a descriptive-analytic survey was conducted with a quantitative and qualitative approach. Analytical protocols were formulated to determine how ideational, interpersonal and textual meanings were produced and how the photographic image and the verbiage were articulated in a single frame. These instruments were applied to a set of 100 micro texts taken from a newspaper with daily publication. Complementing were collected texts in the digital environment. The contexts of situation and of culture (HALLIDAY; HASAN, 1989; EGGINS; MARTIN, 1998) were identified and then lexicogrammatical and visual choices in the systems of the TRANSITIVITY and of the THEME (HALLIDAY; MATTHIESSEN, 2004, 2014) have been mapped. Interpersonal meanings were treated with the categories social distance, contact, status and power (KRESS; VAN LEEUWEN, 2006). In adition, the interaction between verbal and visual modes was analyzed in terms of symmetric / asymmetric relations and logical-semantic (SALWAY; MARTINEC, 2005). The data show that the micro verbal-visual chronic has the social purpose to share a personal impression of a topic considered socially relevant from the view of the author that interprets the photographic representation of meanings pertaining to everyday discourse. This setting identifies the micro verbal-visual chronic with the observation, a genre of the story sistem. The generic structure of a micro verbal-visual chronic consist of the presentation of a photographic image and its verbal interpretation. The obligatory stages are Setting ^ Comment with three additional optional stages ((Appreciation) / (Locution) / (Idea)).